The Development of School Readiness of Kindergarten Students Through Storytelling - Arina Mufrihah; Luthfatun Nisa' (Universitas Islam Tribakti Lirboyo Kediri, 2021)
Complete–playtime is an early concept of kindergarten idea. However, recently, children no longer obtain many opportunities to explore themselves through contextual learning activities such as playing drama or listening to tale. Children are focused on academic-centered activities, so they experience learning boredom at an early age. Moreover, students have not owned a school readiness when entering elementary school. This research helps kindergarten students have school readiness like academic skill, emotional-social skill, and morality through storytelling classically. This experimental study used True-Experimental Postest-Only Design. The two kindergartens were selected through cluster sampling from 100 target populations—the data was collected using the Bender Gestalt Test and observation. The series of storytelling activities as a treatment given towards students proved that the experimental group had school readiness earlier than the controlled group. The experimental group possessed more school readiness than the control group, with the difference was 37% age equivalent to eight years old and 29.6% equal to 7 years old. Other purposes accomplished were developing school readiness skills in vocabulary building, active question-answering, positive attitude towards peers, concern towards social environment, and literacy development.